The First Case of Infectious Spondylitis Caused by Gemella bergeri - Kyoung Ree Lim; Jun Seong Son; Soo-youn Moon (Medicina, 2023)
Gemella bergeri, a member of the genus Gemella, is a facultatively anaerobic, Gram-positive cocci. G. bergeri is a component of normal oral flora; however, it can become pathogenic and cause infections in patients with poor oral hygiene. A 78-year-old man was admitted to a hospital with a complaint of increasing posterior neck pain and lower back pain for 2 weeks. MRI was suggestive of infectious spondylitis at the C3-C4 level with prevertebral abscess formation, anterior epidural abscess formation. We identified Gemella bergeri in closed pus obtained during the surgery. Herein, we describe the first case of infective spondylitis caused by G. bergeri.